SHARIA EQUITY CROWDFUNDING MODEL WAQF - Syawal Harianto; Mizan Mizan; Haris Al Amin; Abdul Halim (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
The concept of inclusive finance in the fintech era encourages Islamic banking to improve the quality and innovation of technology-based products. Currently, the development of financial technology is starting to move towards the digitization of financial institutions The purpose of this research is: first, to know the concept of Sharia equity crowdfunding in Indonesia from the perspective of sharia compliance; second, to find out the implementation of crowdfunding-sharia from the perspective of shariah compliance. The method used by researchers is the thematic approach method. The results of this study show that transactions in the concept of Sharia equity crowdfunding can be developed and granted but must be in accordance with sharia compliance with the orentation of economic transactions in the real sector. As for the agreement that can be used in the form of mudharabah, musyarakah, salam, ijarah, and qard, The field of construction/agriculture/agricultural plantations can be a partner (mudharib). The implementation of the sharia equity crowdfunding (SEC) model must still pay attention to risk management and legal issues and become an alternative solution for Islamic banks. Based on the findings of this study, the following recommendations are made: Islamic banking must innovate products using the SEC model to reach MSMEs and startups through the use of mobile platforms and collaboration with fintect; improve SEC literacy and socialization of Sharia economy through financial technology; sec.The SEC model can be an alternative to my banking innovation in financial instruments by targeting MSMEs, startups. By supporting the implementation of the SEC model, it is expected that there will be technological modernization and improvement in the quality of Islamic banking human resources.